Anomalous left coronary artery from the pulmonary artery - what we know about the disease 90 years after its discovery by Bland, White, and Garland - Wasilewski, Marcin; Moszura, Aleksandra; Skwara, Julia; Nowicki, Maciej; Barański, Dawid; Salińska, Anna; Laskowski, Gustaw; Dąbrowska, Natalia; Węgrzyn, Piotr; Węgrzyn, Konstancja; Góra, Agnieszka; Kurzyna, Paweł (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital coronary anomaly associated with a mortality rate of 90% within the first year of life, with diagnosis occurring in only 10% to 15% of patients during adulthood. ALCAPA is subdivided into infant type and adult type. While angiography remains the diagnostic gold standard, echocardiography serves as a convenient, non-invasive, and highly reliable initial step in suspected cases of ALCAPA. Computed tomography and magnetic resonance imaging are also capable of providing a definitive diagnosis. Surgical management aims to establish a dual-coronary system through various techniques, with goals including gradual improvement in left ventricular function and reduction in mitral regurgitation. In selected cases, consideration may also be given to mitral valvuloplasty or placement of an implantable cardioverter defibrillator. Postoperatively, patients should undergo regular follow-up evaluations to monitor cardiac function and detect any complications.